Financial Performance, Exchange Rate and Stock Return: Evidence from Manufacturing Sector - Perdana Wahyu Santosa (Jurnal Manajemen Teknologi, 2019)
Abstract This study aims to find out and understand what variables influence stock returns on the Indonesia Stock Exchange. Stock return is the first and foremost consideration for investors in making investment decisions, besides fundamental factors and the business environment. The methodology uses financial data with a sample of manufacturing companies recorded in the period 2013-2018, on the Indonesia Stock Exchange. The analysis used multiple regression analyisis and moderated regression analysis (MRA) for before and after mediating the IDR-USD exchange rate. The findings obtained are before being moderated, and after being mediated shows the liquidity (CR), efficiency (TATO), profitability (ROA and EPS), and solvency (DER) proxy, have a significant effect on stock returns, both before and after being mediated. Thus, it is evident that the exchange rate can influence financial performance factors, both partially and simultaneously. Managerial implications: capital market practitioners, especially investors/asset managers, can consider the variables and observe the movements of the IDR-USD exchange rate above as a component of investment decision making.Keywords: Stock return, financial performance, liquidity, efficiency, profitability, solvency, exchange rateAbstrak Studi ini bertujuan untuk mengetahui dan memahami variabel apa saja yang bepengaruh terhadap return saham di Bursa Efek Indonesia. Return saham merupakan pertimbangan pertama dan utama bagi invstor dalam mengambil keputusan investasinya, di samping aspek fundamental dan lingkungan bisnis. Metodologi menggunakan data finansial dengan sampel perusahaan manufaktur sektor Barang Konsumsi yang tercatat pada periode 2013-2018, di Bursa Efek Indonesia. Analisis menggunakan regresi berganda dan moderated regression analysis (MRA) untuk sebelum dan sesudah termoderasi nilai tukar IDR-USD. Temuan yang didapat adalah sebelum termoderasi dan sesudah dimediasi menunjukkan proksi likuiditas (CR), efisiensi (TATO), profitabilitas (ROA dan EPS), dan solvabilitas (DER), berpengaruh signifikan terhadap return, baik sebelum maupun sesudah dimoderasi. Dengan demikian, terbukti bahwa nilai tukar mampu mempengaruhi faktor-faktor kinerja finansial, baik secara parsial maupun simultan. Implikasi manajerial: praktisi pasar modal terutama investor/manajer aset dapat mempertimbangkan variabel-variabel serta mengamati pergerakan nilai tukar IDR-USD sebagai komponen pengambilan keputusan investasi.Kata kunci: Return, likuiditas, efisiensi aset, profitabilitas, solvabilitas, nilai tukar.